2023
DOI: 10.3390/app13095536
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Positive Pressure Ventilator Setting Distance in Front of the Doorway on the Effectiveness of Tactical Mechanical Ventilation in a Multistory Building

Abstract: Proper positioning of the positive pressure ventilator is an important aspect of conducting rescue operations. The purpose of this article was to determine the effect of the parameter of the distance of setting up a mobile fan (distance from 1 to 7 m) on the efficiency of implemented ventilation in a multistory building. The volumetric airflow rate was determined by measuring the flow velocity at 120 measurement points on the surface of the window opening (which served as the measurement plane) of a four-story… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Positive pressure ventilators producing an air stream with a lower degree of turbulence (e.g. having flow rectifiers), do not lose their momentum intensively (deceleration reduction), are able to blow a stably directed stream over longer distances (even 5–7 m) 28 , 29 . Positive pressure ventilators characterized by greater flow turbulence, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive pressure ventilators producing an air stream with a lower degree of turbulence (e.g. having flow rectifiers), do not lose their momentum intensively (deceleration reduction), are able to blow a stably directed stream over longer distances (even 5–7 m) 28 , 29 . Positive pressure ventilators characterized by greater flow turbulence, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…conventional fan, (if set at distances above 1 m) may work with lower efficiency—the stream generated by the ventilator will begin to slow down as a result of adding additional air from the environment. Such a jet can also change the flow direction and asymmetrically flow onto the surface of the inlet opening 28 , 29 . where:
Figure 10 Percentage reduction of air flow depending on positive pressure ventilator setting, where: ( a )—1, ( b )—2, ( c )—3, ( d )—4, L—distance of the fan from the door opening, α—angle of inclination of the impeller axis from the ground.
…”
Section: Resultsmentioning
confidence: 99%
“…2023 studied identical ventilator units. During these tests, it was shown that the effectiveness of such a ventilator decreases as the positioning distance relative to the doorway increases 10 . The same conclusions were also proposed by Lougheed et.…”
Section: Volumetric Airflowmentioning
confidence: 99%
“…The obtained results, confirmed that in the context of flow resistance, in addition to secondary pressure losses associated with friction against the facility's interior walls, interaction of stair treads and changes in flow direction, the main sources of flow resistance in the facility are constrictions (openings in the ceiling) between floors. In addition, the authors showed that if the intention to be achieved during the rescue operations is to increase the value of the flow rate, it is more important to reduce the resistance to flow in the building or increase the value of the pressure than to increase the discharge area [10][11] . An interesting full-scale study of positive pressure ventilators was also conducted by Lambert et al in 2018. The tests concerned the evaluation of the flow rate of a set of ventilators, on the site of a facility that constitutes subway stations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation